Evaluation of collaborative models of care in the management of patients with depression: protocol and progress - Ali Afzali, Hossein Haji (Radcliffe Publishing Ltd., 2012)
Introduction Depression is highly prevalent and has a considerable impact on the quality of life of affected individuals, and on healthcare resources. Evidence indicates that collaborative care models can improve patient outcomes within a primary care setting. The Primary Care Services Improvement Project (PCSIP) aims to investigate the costs and outcomes of different models of care for the management of patients with depression. These models have been defined based on the level of involvement of practice nurses in management processes within the primary care setting in Australia. This paper describes our study protocol and its progress. Methods PCSIP is an observational study that will link retrospective data from a range of sources to estimate costs and intermediate outcomes (such as relapse rate) over a 3-year time horizon. The main sources of primary data include the medical records of patients held at participating practices and Medicare Australia. Initial report We recruited 15 practices from a metropolitan area and allocated them to three models of care. Two hundred and sixty-one patients agreed to participate. Appropriate regression-based analyses will be used to evaluate the association between different models of care and patient-level outcomes while controlling for several covariates such as age and gender. Discussion/conclusions This project will generate the knowledge required to promote investment in the most cost-effective initiatives, and to ensure that waste of resources due to the implementation of comparatively inefficient interventions is minimised. Given the scarcity of resources, the increasing costs of providing healthcare and the increasing prevalence of chronic diseases, such research is essential.